Immunodominance of HLA-A2-Restricted Hepatitis C Virus-Specific CD8 + T Cell Responses Is Linked to Naïve-Precursor Frequency - Julia Schmidt; Christoph Neumann‐Haefelin; Tayibe Altay; Emma Gostick; David A. Price; Volker Lohmann; Hubert E. Blum; Robert Thimme (2011)
ABSTRACT The impact of naïve-precursor frequency on human virus-specific CD8 + T cell immunodominance is not well understood. Using a recently developed major histocompatibility complex (MHC) class I tetramer enrichment protocol, we found a conserved hierarchy and a >10-fold difference in naïve-precursor frequencies across three HLA-A2-restricted hepatitis C virus (HCV)-specific epitopes. Importantly, the NS3 1406 epitope with the highest naïve-precursor frequency in healthy donors was also the most frequently targeted epitope in a large cohort of chronically HCV-infected patients, both ex vivo and after in vitro stimulation. These results indicate for the first time that immunodominance in a human viral infection is linked to naïve-precursor frequency.